Developing career self-management skills : a study in higher education - Pinto, Joana Carneiro (2013)
This study aims to evaluate the Career Self-Management Seminar, version B. This is a psychological intervention model, developed to support PhD students in the improvement of crucial skills for effective career problem solving and decision making. Sample included 63 PhD’s, (49 experimental group, 14 control group), from both sexes (44 women, 19 men), and with ages ranging from 22 to 49 years old (M=29.7; SD=6.74). These participants were assessed on the career exploration and career concern dimensions, through the completion of the Portuguese versions of the Career Exploration Survey and of the Adult Career Concerns Inventory respectively, at three different moments in time (pre-test, post-test and follow-up). Results demonstrated that the CSMS-B is effective in promoting external instrumentality beliefs, and self and environment exploration, and also in diminishing concerns and needs about the deceleration and reduction of their current professional role. Future studies should invest in the development and assessment of career self-management interventions aimed at students attending higher education.